The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.chemmater.9b03779
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modulating the Twist Rate of Helical van der Waals Crystals

Abstract: Twisted van der Waals (vdW) materials with a controllable twist are of great interest because the twist offers new opportunities to modify the optoelectronic properties of the materials, giving rise to exotic phenomena, such as superconductivity, moiré excitons, and chiroptical response. Recently, we have synthesized helical vdW crystals with a periodic twist via the vapor–liquid–solid (VLS) growth of dislocated germanium sulfide nanowires with an Eshelby twist. The twist rates and periods of these structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The initial diameter of spiral nanowires is equivalent to the droplet size, which could be adjusted by controlling the concentration and the composition of precursors to tune the twist rate and period length, as the entry of precursor affect the surface tension of the alloy droplet. [ 22,138,141 ] At higher temperatures, the droplet solubility becomes higher, corresponding to a larger initial diameter and period length of spiral nanowires. [ 142 ] Other growth mechanisms, such as LBL growth and twin‐driven growth, sometimes occur, for the orientation and facets of initial whiskers in contact with the droplet are determined by the alloy components.…”
Section: Spiral Nanowiresmentioning
confidence: 99%
“…The initial diameter of spiral nanowires is equivalent to the droplet size, which could be adjusted by controlling the concentration and the composition of precursors to tune the twist rate and period length, as the entry of precursor affect the surface tension of the alloy droplet. [ 22,138,141 ] At higher temperatures, the droplet solubility becomes higher, corresponding to a larger initial diameter and period length of spiral nanowires. [ 142 ] Other growth mechanisms, such as LBL growth and twin‐driven growth, sometimes occur, for the orientation and facets of initial whiskers in contact with the droplet are determined by the alloy components.…”
Section: Spiral Nanowiresmentioning
confidence: 99%
“…The twist rates and periods of the structures are determined by the radii of the dislocated nanowires that are defined by the size of the Au-Ge alloy droplets catalyzing the vapor-liquid-solid (VLS) process. Through introducing germanium selenide (GeSe) into the growth, the droplet size was chemically tuned and thereby the twist rate and period of the twisted structures 52 . The chemical modulation demonstrates good potential to tailor the twist rate and period of helical vdW crystals, enabling a new degree of freedom to modulate optical, electrical, thermal, mechanical and catalytic properties.…”
Section:  =mentioning
confidence: 99%
“…In our previous study, , we found that an axial dislocation in GeS nanowires (NWs) can induce a continuous twist along the substrate, known as Eshelby twist. Further growth along the radical direction leads to helical MWs, consisting of discretely twisted nanoplates.…”
mentioning
confidence: 99%
“…Figure e shows the Raman spectra of helical GeS MWs and GeSe/GeS heterostructures, respectively. The characteristic Raman modes are labeled, which can be categorized to GeS and GeSe. ,, We also perform detailed miro-X-ray diffraction measurements on helical GeS and GeSe/GeS MWs (see Figure S6 for details), showing that the epitaxial GeSe is of the same crystallinity and orientation as the helical GeS template. All these characterizations suggest that our facile edge epitaxy method effectively serves for preparing high-quality GeSe/GeS heterostructures with helicoidal morphology.…”
mentioning
confidence: 99%